Müntz Rational Approximation for Special Function Classes in $Ba[0, 1]$ Spaces (Analysis in Theory and Applications, 2012)
In this paper, we research the Müntz rational approximation of two kinds of special function classes, and give the corresponding estimates of approximation rates of these classes.
Keywords: Müntz rational approximation; bounded variation function class; Sobolev function class; approximation rate.